The role of promoter cis-element, mRNA capping, and ROS in the repression and salt-inducible expression of AtSOT12 in Arabidopsis - Chen, Jinhua; Wang, Bangshing; Chung, Jung-Sung; Chai, Haoxi; Liu, Chunlin; Ruan, Ying; Shi, Huazhong (Frontiers in Plant Science, 2015)
Inducible gene expression is a gene regulatory mechanism central to plant response to environmental cues. The inducible genes are often repressed under normal growth conditions while their expression levels are significantly elevated by conditions such as abiotic stresses. Induction of gene expression requires both cis-acting DNA elements and trans-acting proteins that are modulated through signal transduction pathways. Here we report several molecular events that affect salt induced expression of the Arabidopsis AtSOT12 gene. Promoter deletion analysis revealed that DNA elements residing in the 5’ UTR are required for the salt induced expression of AtSOT12. Cytosine methylation in the promoter was low and salt stress slightly increased the DNA methylation level, suggesting that DNA methylation may not contribute to AtSOT12 gene repression. Co-transcriptional processing of AtSOT12 mRNA including capping and polyadenylation site selection was also affected by salt stress. The percentage of capped mRNA increased by salt treatment, and the polyadenylation sites were significantly different before and after exposure to salt stress. The expression level of AtSOT12 under normal growth conditions was markedly higher in the oxi1 mutant defective of ROS signaling than in the wild type. Moreover, AtSOT12 transcript level was elevated by treatments with DPI and DMTU, two chemicals preventing reactive oxygen species (ROS) accumulation. These results suggest that repression of AtSOT12 expression may require physiological level of ROS and ROS signaling.